Declining autonomy at work in the EU and its effect on civic behaviour - Lopes, H.; Lagoa, S.; Calapez, T. (Economic and Industrial Democracy, 2014)
The aim of this article is to show that social benefits may accrue from work environments that support autonomous forms of work. Based on social psychology, economics and philosophy approaches, the authors argue that autonomy is a basic human need which, when satisfied, enhances civic behavior. Using individual data from the EWCS, the article finds evidence of the positive effect of work autonomy on volunteer work and political/trade union activities. Overall, work autonomy has decreased over the last 15 years for all skill levels in the EU, though there are substantial differences between countries. Organizational practices that promote autonomy should be deliberately stimulated if civic participation is to be furthered.